Genetic variability and associations among yield and certain yield components in forty clones of rubber - Mydin K K; Nair V G; Panikkar A O N; Saraswathy P; Sethuraj M R (Placrosym XI,Calicut,India, 1994. Journal of Plantation Crops, 24 (Supplement); 403-412, 1996)
Forty clones of rubber were evaluated for the extent of variability for yield and certain yield components at the fourth year of tapping. Highly significant clonal variation was evident for all the traits studied enabling the identification of clones superior for each yield component. Genotypic correlations with volume of latex, dry rubber content, latex flow rate, girth, girth increment and bark thickness and negatively correlated with plugging index and yield depression under stress. Employing the discriminant function technique, eleven clones with high selection indices were identified as potential parents for future breeding programmes.
Keywords: Genetic variability; Yield